Decrease in breast cancer incidence following a rapid fall in use of hormone replacement therapy in Australia. - Canfell, K; Banks, E; Moa, A; Beral, V (2008)
OBJECTIVE: To determine if the recent rapid fall in use of hormone replacement therapy (HRT) in Australia has been followed by a reduction in breast cancer incidence among women aged 50 years or older, but not among younger women. DESIGN AND SETTING: Analysis of trends in annual prescribing of HRT, using Pharmaceutical Benefits Scheme data, and in annual age-standardised breast cancer incidence rates in Australian women for the period 1996-2003. RESULTS: In Australia, prescribing of HRT increased from 1996 to 2001, but dropped by 40% from 2001 to 2003. Age-standardised breast cancer incidence rates in women aged > or = 50 years also increased to 2001 but declined thereafter. The incidence rates in this age group were lower by 6.7% (95% CI, 3.9%-9.3%; P < 0.001) in 2003 compared with 2001, equivalent to 600 (95% CI, 350-830) fewer breast cancers (out of about 9000 incident breast cancers annually for women this age). There was no significant change in breast cancer incidence for women aged < 50 years. CONCLUSIONS: While other factors may have contributed to a recent reduction in breast cancer incidence among Australian women aged > or = 50 years, the available evidence suggests that much of the decrease is due to the recent fall in use of HRT. This is consistent with other evidence that the HRT-associated increase in risk of breast cancer is reversible after ceasing use of HRT.